(untitled) (Global Journal of Science Frontier Research, 2014)
The aim of this study is to assess seawater quality and impacts of traditional ritual ceremonies on foremost seashore Navagraha temple. The seawater samples were collected at seven different station and water quality parameters were analyzed on the standard methods. Physico-chemical parameter; pH, electrical conductivity, temperature, total suspended solids, total dissolved solids, total solids, biological oxygen demand, sulphate and microbiological indicators; total heterotrophic bacterial count, total fungal count, total actinomycetes count, and total enteric bacterial count were performed. These results indicated that the water highly exceeds the Indian primary seawater quality standards criteria-II. To prove this hypothesis unregulated celebrations of religious ceremonies are highly polluting the seawater and it cause significant adverse impact on human and marine biota. Our results can provide the potential value for alternative ritual activities and calls for urgent intervention by government management policy on a local and regional support future policy decisions and awareness.